Changes in soil water availability and air-temperature impact biomass allocation and C:N:P stoichiometry in different organs of Stylosanthes capitata Vogel. (15th January 2021) - Olivera Viciedo, Dilier; de Mello Prado, Renato; Martinez, Carlos Alberto; Habermann, Eduardo; de Cássia Piccolo, Marisa; Calero Hurtado, Alexander; Barreto, Rafael Ferreira; Peña Calzada, Kolima
Abstract: Temperature and soil water availability play important roles in the biogeochemical cycles of essential elements for plant growth, such as carbon (C), nitrogen (N), and phosphorus (P). In this study, we investigated how drought and warming impact C:N:P stoichiometric ratios of different plant organs (leaves, inflorescences, and stems), and biomass allocation and production of a field-grown pasture of Stylosanthes capitata, a tropical forage legume . We evaluated the effects of elevated temperature (+2 °C above ambient temperature) under two conditions of soil water availability, irrigated, and non-irrigated. In general, we observed that different functional plant organs showed distinct responses to drought and warming demonstrating how important is to evaluate different functional plant organs to unravel crop nutrient dynamics. In addition, interactive effects between warming and drought were observed in many situations, highlighting the importance of multifactorial studies. Our data showed that warming produced plants with more inflorescences, decreasing leaf:inflorescence ratio. However, only warming under well-watered conditions improved biomass production (in 38%). Warmed and irrigated plants showed higher stoichiometric homeostasis compared to other treatments. In an opposite direction, drought decreased P concentration and increased N:P ratios in different organs, reducing the stoichiometric homeostasis under both conditions of temperature. We have concluded that warm and well-watered conditions without restrictions in soil nutrient availability can enhance plant production, presumably due to a higher level of stoichiometric homeostasis. Graphical abstract: Image 1 Highlights: Water stress and high temperature decrease leaf:inflorescence and leaf:stem ratios. Drought conditions decreased P concentrations and increased N:P ratio. The N and P allocations differed remarkably between plant organs. Drought and warming had significant interactive effects on foliar N and P but not C. Warming combined with well-watered conditions increased leaf biomass production up 38%.